709 Exosome surface display of IL-12 results in tumor-retained pharmacology with superior potency and limited systemic exposure. (10th December 2020) - Lewis, Nuruddeen; Sia, Chang Ling; Kirwin, Katherine; Haupt, Sonya; Mahimkar, Gauri; Zi, Tong; Xu, Ke; Dooley, Kevin; Jang, Su Chul; Choi, Bryan; Grube, Andrew; McCoy, Christine; et al.
Abstract : Background: The promise of Interleukin-12 as a cancer treatment has yet to be fulfilled with multiple tested approaches being limited by unwanted systemic exposure and unpredictable pharmacology. To address these limitations, we generated exoIL-12™, a novel, engineered-exosome therapeutic that displays functional IL-12 on the surface of an exosome. Methods: IL-12 exosomal surface expression was achieved via fusion to the abundant exosomal surface protein PTGFRN. Potency was assessed in vitro using human PBMCs or murine splenocytes and in vivo using mouse subcutaneous tumor models. Local versus systemic pharmacology was determined with intratumoral injection in mice and subcutaneous injection in monkeys. All studies were benchmarked against recombinant IL-12 (rIL-12). Results: Exosomes engineered to express either murine or human IL-12 had equivalent potency in vitro to rIL-12 as demonstrated by IFNγ production. Following intratumoral injection, exoIL-12 exhibited prolonged tumor retention and greater antitumor activity than rIL-12. Moreover, exoIL-12 was 100-fold more potent than rIL-12 in tumor growth inhibition. In the MC38 tumor model, complete responses were observed in 63% of mice treated with exoIL-12; in contrast, rIL-12 resulted in 0% complete responses at an equivalent IL-12 dose. This correlated with dose-dependent increases in tumor antigen-specific CD8+ T cells. Re-challenge studies of exoIL-12 in complete responder mice showed no tumor regrowth. Moreover, depletion of CD8+ T cells completely abrogated the antitumor activity of exoIL-12. Following intratumoral administration, exoIL-12 exhibited 10-fold higher intratumoral exposure than rIL-12 and prolonged IFNγ production up to 48 hr. Retained, local pharmacology of exoIL-12 was further confirmed using subcutaneous injections in non-human primates. Conclusions: This work demonstrates that tumor-restricted pharmacology of exoIL-12 results in superior in vivo efficacy and immune memory without systemic IL-12 exposure and related toxicity. exoIL-12 is a novel cancer therapeutic candidate that has the potential to overcome key limitations of rIL-12 and thereby create a therapeutic window for this potent cytokine. Ethics Approval: All animals were maintained and treated at the animal care facility of Codiak Biosciences in accordance with the regulations and guidelines of the Institutional Animal Care and Use Committee (CB2017-001).